Changes in Male Rat Sexual Behavior and Brain Activity Revealed by Functional Magnetic Resonance Imaging in Response to Chronic Mild Stress. Issue 2 (20th December 2017) - Chen, Guotao; Yang, Baibing; Chen, Jianhuai; Zhu, Leilei; Jiang, Hesong; Yu, Wen; Zang, Fengchao; Chen, Yun; Dai, Yutian
Abstract: Background: Non-organic erectile dysfunction (noED) at functional imaging has been related to abnormal brain activity and requires animal models for further research on the associated molecular mechanisms. Aim: To develop a noED animal model based on chronic mild stress and investigate brain activity changes. Methods: We used 6 weeks of chronic mild stress to induce depression. The sucrose consumption test was used to assess the hedonic state. The apomorphine test and sexual behavior test were used to select male rats with ED. Rats with depression and ED were considered to have noED. Blood oxygen level-dependent–based resting-state functional magnetic resonance imaging (fMRI) studies were conducted on these rats, and the amplitude of low-frequency fluctuations and functional connectivity were analyzed to determine brain activity changes. Outcomes: The sexual behavior test and resting-state fMRI were used for outcome measures. Results: The induction of depression was confirmed by the sucrose consumption test. A low intromission ratio and increased mount and intromission latencies were observed in male rats with depression. No erection was observed in male rats with depression during the apomorphine test. Male rats with depression and ED were considered to have noED. The possible central pathologic mechanism shown by fMRI involved the amygdaloid body, dorsal thalamus, hypothalamus, caudate-putamen, cingulate gyrus, insular cortex, visual cortex, sensory cortex, motor cortex, and cerebellum. Similar findings have been found in humans. Clinical Translation: The present study provided a novel noED rat model for further research on the central mechanism of noED. Strengths and Limitations: The present study developed a novel noED rat model and analyzed brain activity changes based at fMRI. The observed brain activity alterations might not extend to humans. Conclusion: The present study developed a novel noED rat model with brain activity alterations related to sexual arousal and erection, which will be helpful for further research involving the central mechanism of noED.